An efficient photo-catalytic VOC removal process by one-pot synthesized N-F/TiO2 nanoparticles in fluidized-spouted bed reactor. (17th February 2018) - Mansoubi, Hadi; Fatemi, Shohreh; Mansourpour, Zahra
ABSTRACT: Photocatalytic degradation under visible light irradiation is an important task of using solar energy for the removal of environmental pollutants. N-F/TiO2 nanoparticles were synthesized in one-pot sol–gel condition using tetra-isopropyl-orthotitanate as the TiO2 precursor and NH4 F as the N-F doping source. Diffuse reflectance spectroscopy (DRS) analysis of the material has shown a reduction of band gap energy and shifting absorption edge to the visible wavelengths. A fluidized-spouted bed reactor equipped with the light source was designed and constructed for the oxidation process of VOC from the high airflow rate under Hg lamp irradiation using synthesized N-F/TiO2 nanoparticles. Acetaldehyde was used as the air pollutant model molecule of VOC in this process. The effluent acetaldehyde concentration was analyzed continuously along the time by an online Gas Chromatography (GC) from the start up to reaching steady conditions. The results have revealed significant enhancement of acetaldehyde removal by the N-F/TiO2 sample fabricated with an equal weight ratio of NH4 F/Ti. After steady conditions, almost 100% removal of acetaldehyde was observed in the spouted bed reactor from a high airflow stream of 5 L/min polluted with 1000 ppm acetaldehyde at room-temperature conditions, under 80 W Hg with 500 Lux intensity.